Peran Mahasiswa KKN Unusia Dalam Membangun Desa Bertumbuh Dan Berkembang Untuk Desa Cibeuteung Muara, Kecamatan Ciseeng, Kabupaten Bogor, Provinsi Jawa Barat - Lailatul Irodatis Sya’diyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
The Real Work Lecture Program (KKN) is a form of education in the pattern ofcommunity service. KKN Rajendra Team are doing of community service in CibeuteungMuara Village RT 002 RW 003, Ciseeng District, Bogor Recency West Java Province hasthe aim of building a growing developing village while providing knowledge andunderstanding to the community about the importance of early education. The programthat can support it is the socialization of education to all lines of the village community,both those in schools and parents as well as village officials. Therefore, through thisKKN students help in community education or community empowerment located inCibeuteung Muara Village.Keywords : Village, Education, Socialization.